PNA-Modified Liposomes Improve the Delivery Efficacy of CAPIRI for the Synergistic Treatment of Colorectal Cancer - Diao, Wenbin; Yang, Ben; Sun, Sipeng; Wang, Anping; Kou, Rongguan; Ge, Qianyun; Shi, Mengqi; Lian, Bo; Sun, Tongyi; Wu, Jingliang; Bai, Jingkun; Qu, Meihua; et al. (Frontiers in Pharmacology, 2022)
Tumor-associated antigen mucin 1 (MUC1) is highly expressed in colorectal cancer and is positively correlated with advanced stage at diagnosis and poor patient outcomes. The combination of irinotecan and capecitabine is standard chemotherapy for metastatic colorectal cancer and is known as XELIRI or CAPIRI, which significantly prolongs the progression-free survival and overall survival of colorectal cancer patients compared to a single drug alone. We previously reported that peanut agglutinin (PNA)-conjugated liposomes showed enhanced drug delivery efficiency to MUC1-positive liver cancer cells. In this study, we prepared irinotecan hydrochloride (IRI) and capecitabine (CAP)-coloaded liposomes modified by peanut agglutinin (IRI/CAP-PNA-Lips) to target MUC1-positive colorectal cancer. The results showed that IRI/CAP-PNA-Lips showed an enhanced ability to target MUC1-positive colorectal cancer cells compared to unmodified liposomes. Treatment with IRI/CAP-PNA-Lips also increased the proportion of apoptotic cells and inhibited the proliferation of colorectal cancer cells. The targeting specificity for tumor cells and the antitumor effects of PNA-modified liposomes were significantly increased in tumor-bearing mice with no severe cytotoxicity to normal tissues. These results suggest that PNA-modified liposomes could provide a new delivery strategy for the synergistic treatment of colorectal cancer with clinical chemotherapeutic agents.